MODEL PEMBELAJARAN INOVATIF DALAM PAI DAN PERBANDINGAN MODEL PEMBELAJARAN INOVATIF DENGAN MODEL PEMBELAJARAN KLASIK - Rahimah, Rahimah; Fahrizal Akbar, Ahmad; Cahyadi, Ani (CV. Lafadz Jaya, 2024)
Learning Islamic Religious Education (PAI) requires innovation in learning models to increase effectiveness and attract students' interest. Some innovative learning models that can be applied in Islamic Education include Cooperative Learning, Problem-Based Learning, Project-Based Learning, Inquiry-based learning, Flipped Classroom, and Blended Learning. These models emphasize active learner participation, real problem solving, group work, and linking material to everyday life. Innovative learning models are different from classic teacher-centered learning models. In innovative models, learners play a more active role in the learning process, while the teacher acts as a facilitator. In addition, innovative models are more flexible, interactive and prioritize the development of higher-order thinking skills. Compared to the classic model which tends to be monotonous and one-way, the innovative model is more interesting, challenging and in line with the times and the needs of today's learners. The application of innovative learning models in PAI is expected to improve students' understanding and skills, as well as instill Islamic values in a more meaningful and contextual manner. However, the successful application of innovative models is highly dependent on the readiness and ability of teachers to design, implement, and evaluate the learning process effectively.